Migration and Satisfaction: The Case of Hilly to Terai Region - Baruwal , Himal (Bhairahawa Campus Journal, 2023)
This article proposes a formal model of migration in which people of hilly area migrated to Terai area. Migration was taken place for the betterment of life, nuclear family choice, risk of financial management, adjustment adverse climatic condition, cultural and social differences. It shows that migration can be take place in various adverse situation and risk, surprisingly, when earning is more and less in both situations, migration can take place. I provide some evidence in support of the concerned area.